Back-table procedure and auto-lung transplantation for locally advanced lung cancer: a case report. Issue 1 (December 2016) - Karube, Yoko; Chida, Masayuki; Nishihira, Morimichi; Inoue, Takashi; Araki, Osamu; Kobayashi, Satoru; Sado, Tetsu
Abstract Background To avoid a pneumonectomy and preserve the lung parenchyma, a bronchovascular double-sleeve plasty including an extended sleeve lobectomy is a good choice for locally advanced lung cancer. Case presentation We describe a case with lung adenocarcinoma enrolled in our new protocol forex situ auto-lung transplantation following anen bloc pneumonectomy and back table procedure for central lung cancer. Following completion of the pneumonectomy, the excised lung was irrigated with a cold extracellular phosphate-buffered solution to protect the lung graft from ischemia-reperfusion injury during preparation of the graft of a right basal segment as a back-table procedure. Conclusion Although auto-lung transplantation is a complicated procedure, anen bloc pneumonectomy following a back table procedure makes preparation of the graft easy, while simultaneous mediastinal lymph node dissection by another surgeon shortens operation time.